2022
DOI: 10.5194/tc-16-3215-2022
|View full text |Cite
|
Sign up to set email alerts
|

TermPicks: a century of Greenland glacier terminus data for use in scientific and machine learning applications

Abstract: Abstract. Marine-terminating outlet glacier terminus traces, mapped from satellite and aerial imagery, have been used extensively in understanding how outlet glaciers adjust to climate change variability over a range of timescales. Numerous studies have digitized termini manually, but this process is labor intensive, and no consistent approach exists. A lack of coordination leads to duplication of efforts, particularly for Greenland, which is a major scientific research focus. At the same time, machine learnin… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 71 publications
0
16
0
Order By: Relevance
“…This glacier, located at 66.48°N, 36.72°W, takes various names: most commonly Midgard Glacier (Moon et al, 2014;Mouginot et al, 2019), but also Franche Comté Glacier (Bjørk et al, 2015;Goliber et al, 2022;Vijay et al, 2019) or Midgard North (Walsh et al, 2012;Williams, 2021). This glacier extended 10 km farther down its fjord as recently as 2002, but since has retreated rapidly and split into two glaciers around 2012 (Korsgaard, 2021).…”
Section: Midgard (Franche Comté) Glaciermentioning
confidence: 99%
See 1 more Smart Citation
“…This glacier, located at 66.48°N, 36.72°W, takes various names: most commonly Midgard Glacier (Moon et al, 2014;Mouginot et al, 2019), but also Franche Comté Glacier (Bjørk et al, 2015;Goliber et al, 2022;Vijay et al, 2019) or Midgard North (Walsh et al, 2012;Williams, 2021). This glacier extended 10 km farther down its fjord as recently as 2002, but since has retreated rapidly and split into two glaciers around 2012 (Korsgaard, 2021).…”
Section: Midgard (Franche Comté) Glaciermentioning
confidence: 99%
“…This glacier separated from Midgard Glacier in 2012 (Korsgaard, 2021). It is significantly smaller and less well studied than the other glaciers in Sermilik Fjord, and many databases omit its name (Bjørk et al, 2015;Mouginot et al, 2019) or refer to it as Midgard South (Williams, 2021) or Midgard Glacier (Goliber et al, 2022;Vijay et al, 2019;Walsh et al, 2012), as it lies directly upfjord of the reach that Midgard used to occupy before its split. The northwestern tributary is significantly larger and we term it Midgard Glacier (Section 3.3).…”
Section: Pourquoi Pas (East Midgard) Glaciermentioning
confidence: 99%
“…Nevertheless, manual front delineation is a very challenging task and underlies a high degree of subjectivity. Having several experts delineating the same front will always generate different results 12,30,33,34 . Hence, the automated front position is not necessarily wrong if it does not align with the manual reference.…”
Section: Technical Validationmentioning
confidence: 99%
“…Much of the Greenland Ice Sheet underwent widespread and rapid outlet glacier retreat in the 2000 s (e.g., Goliber et al., 2022; King et al., 2018), but glaciers along Greenland's east coast showed markedly different behavior during this time (e.g., Carr et al., 2017; Seale et al., 2011; Walsh et al., 2012). Specifically, Seale et al.…”
Section: Introductionmentioning
confidence: 99%
“…Much of the Greenland Ice Sheet underwent widespread and rapid outlet glacier retreat in the 2000 s (e.g., Goliber et al, 2022;King et al, 2018), but glaciers along Greenland's east coast showed markedly different behavior during this time (e.g., Carr et al, 2017;Seale et al, 2011;Walsh et al, 2012). Specifically, Seale et al (2011) examined patterns of frontal retreat for 32 glaciers along the east Greenland coast between 2000 and 2009 and found a distinct contrast between glaciers located south of 69°N compared to those to the north.…”
mentioning
confidence: 99%